A multi-stakeholder foundation for peace in cyberspace. Issue 3 (2nd September 2021) - Ciglic, Kaja; Hering, John
ABSTRACT: In this article we first explore the concept of 'multi-stakeholderism', focusing on how the term was understood when internet governance was first envisioned. We then elaborate on how the concept has evolved in recent years. The focus of the article here, given the shift in how cyberspace is treated by state actors – increasingly as a domain of conflict. We detail how the United Nations (UN) has approached international peace and security online since 2004, via a series of ad hoc working groups that have been largely exclusive to a small number of state participants, and the expansion of interstate conflict online during this same period. The article also introduces a number of informal initiatives that have been spearheaded by multi-stakeholder groups outside the auspices of the UN since 2018 – the Charter of Trust, the Cybersecurity Tech Accord, the Paris Call for Trust and Security in Cyberspace, the Contract for the Web, and the Let's Talk Cyber dialogue series – focusing on the role of the private sector in particular to promote peace and security online. Finally, the article explores what could help ensure that the next generation of cybersecurity dialogues at the UN are structured to address escalating conflict in cyberspace and to take full advantage of external voices in this effort.